Sds22/PP1 links epithelial integrity and tumor suppression via regulation of myosin II and JNK signaling. - Jiang, Y.; Scott, K.L.; Kwak, S.J.; Chen, R.; Mardon, G. (Oncogene, 2011)
Loss of epithelial integrity often correlates with the progression of malignant tumors. Sds22, a regulatory subunit of protein phosphatase 1 (PP1), has recently been linked to regulation of epithelial polarity in Drosophila. However, its role in tumorigenesis remains obscure. In this study, using Drosophila imaginal tissue as an in vivo model system, we show that sds22 is a new potential tumor suppressor gene in Drosophila. Without sds22, cells lose epithelial architecture, and become invasive and tumorigenic when combined with Ras overexpression; conversely, sds22 overexpression can largely suppress tumorigenic growth of Ras(V12)scrib(-/-) mutant cells. Mechanistically, we show that sds22 prevents cell invasion and metastasis by inhibiting myosin II and Jun N-terminal kinase (JNK) activity downstream of PP1. Loss of this inhibition causes cells to lose epithelial organization and promotes cell invasion. Finally, human Sds22 is focally deleted and downregulated in multiple carcinomas, and this downregulation correlates with tumor progression, suggesting that sds22 inactivation may contribute to tumorigenesis and metastatic potential in human cancers via a similar mechanism.